All-round responses and boundaries of a shaft and dry friction damper assembly. (June 2022) - Huang, Zhonghe; Tan, Jianping; Liu, Chuliang; Huang, Shuo
Abstract: A helicopter tailrotor driveline is equipped with dampers to suppress the resonance of transmission shafts. A dry friction damper and a slender shaft form an assembly The comprehensive understanding of different responses of the assembly provides the basis for a more reasonable parameter configuration of the damper. To this end, the assembly is modeled as a dynamic system with rub impact between a rotor with continuous parameter distribution and a suspended elastic stator. Boundaries of rub impact and condition of Hopf bifurcation are derived. Pinned natural frequencies and backward whirl frequencies are solved by analytical deduction. The critical speed for triggering a backward whirl with consideration of eccentric excitation is obtained by the multiple scale perturbation method. Then, all-round responses and boundaries are solved by both analytical and numerical approaches based on the parameters of a helicopter. The effects of friction coefficient, internal damping, suspension stiffness, variable impact stiffness, etc. on the boundaries are presented in detail with the discussion of relationships between physical reasons and analytical conditions. Results show that smaller impact stiffness difference and friction coefficient, a greater mass damping ring, moderate suspension stiffness, greater internal and external damping are the key factors for the damper design. This study has reference significance not only for the assembly in a helicopter but also for similar mechanical systems. Highlights: A rub impact model consisting of a shaft with continuous parameter distribution and a suspended damping ring is proposed. .The appearance condition of backward whirl considering the positive spin excitation is solved by the multiple scale method. Relationships between responses and parameters are present in the aspect of physical reasons and analytical deductions. All-round responses associated with dynamic characteristics and reasonable ranges of the damper's parameters are given.